Cervical cancer screening by high risk HPV testing in routine practice: results at one year recall of high risk HPV-positive and cytology-negative women. (March 2014) - Mistro, Annarosa Del; Frayle, Helena; Ferro, Antonio; Callegaro, Susanna; Sole, Annamaria Del; Stomeo, Anna; Cirillo, Emanuela; Fedato, Chiara; Pagni, Silvana; Barzon, Luisa; Zorzi, Manuel
Objective: Cervical cancer screening by human papillomavirus (HPV) testing requires the use of additional triage and follow-up analyses. We evaluated women's compliance with and the performance of this strategy in a routine setting. Setting: Five cervical service screening programmes in North-East Italy. Methods: Eligible women aged 25-64 invited for a new screening episode underwent HPV testing for high risk types (hrHPV by Hybrid Capture 2) and cytology triage. Women with positive HPV and cytology results were referred for colposcopy; women with positive HPV but negative cytology results were referred to 1-year repeat hrHPV testing. Results: Of 46, 694 women screened by HPV testing up to December 2011, 3, 211 (6.9%) tested hrHPV positive; 45% of these had a positive triage cytology. Those with negative cytology were invited for 1-yr repeat testing. Compliance with invitation was 61.6% at baseline and 85.3% at 1-yr repeat. Rate of persistent hrHPV positivity was 58% (830/1, 435). Colposcopy performed in women with a positive hrHPV test at 1-yr repeat accounted for 36% of all colposcopies performed within the screening programmes. Cumulatively, a histological high-grade lesion was detected in 276 women (5.9‰ detection rate), 234 at baseline (85%), and 42 (15%) at 1-yr repeat. Conclusions: Compliance with hrHPV-based screening programmes was high both at baseline and at 1-yr repeat. Compared with the randomized trials, a higher proportion of triage cytology was read as positive, and only a small number of high-grade lesions were detected among the group of hrHPV positive cytology negative women who repeated testing 1-yr after baseline.